Global Distribution of Concurrent EMIC Waves and Magnetosonic Waves: A Survey of Van Allen Probes Observations. Issue 1 (18th January 2022) - Zhou, Ruoxian; Ni, Binbin; Fu, Song; Teng, Shangchun; Tao, Xin; Hu, Zejun; Guo, Jianguang; Hua, Man; Yi, Juan; Guo, YingJie; Jiao, Luhuai; Ma, Xin; et al.
Abstract: Recent studies have reported the simultaneous observation of Magnetosonic (MS) waves and Electromagnetic ion cyclotron (EMIC) waves. In this study, a detailed survey of the concurrent EMIC waves and MS waves is performed using the Van Allen Probes observations from 2012 to 2017. The results suggest that most of the concurrent EMIC waves and MS waves are H + band EMIC waves and MS waves. The favorable geomagnetic conditions for the concurrent EMIC waves and MS waves are AE* ≥ 500 nT inside the plasmapause and AE* ≥ 100 nT outside the plasmapause. Although EMIC waves are generally stronger than MS waves, stronger MS waves than EMIC waves are more likely to occur during moderate and active geomagnetic times. Our study is consistent with the most recent research, and provides more detailed information that helps us to deepen our understanding of the concurrent EMIC waves and MS waves. Plain Language Summary: Electromagnetic ions cyclotron (EMIC) waves and magnetosonic (MS) waves are two common wave mode in the Earth radiation belts and play important roles in radiation belt dynamics. Recent studies have reported observations of concurrent EMIC waves and MS waves and conducted a brief statistic survey. To deepen our understanding of the concurrent EMIC waves and MS waves, this study aims to comprehensively analyze the statistical occurrence pattern and associated global distribution of concurrent EMIC waves and MS waves. Our study demonstrated that most of the concurrent EMIC waves and MS waves are H+ band EMIC waves and MS waves, which reveals the deep relationship between MS waves and the concurrent H+ band EMIC waves. Our study also demonstrated that the concurrent EMIC waves are generally stronger than MS waves, while the wave amplitudes of MS waves can exceed EMIC waves during geomagnetically turbulent times. This result indicates that the combined scattering effect of the concurrent EMIC waves and MS waves could vary significantly under different geomagnetic conditions. Key Points: Most of the concurrent Electromagnetic ion cyclotron (EMIC) waves and Magnetosonic (MS) waves are H + band EMIC waves and MS waves The concurrent EMIC waves and MS waves are most frequently observed outside the plasmapause under geomagnetic moderate and active conditions The possibility of MS waves stronger than the concurrent EMIC waves is higher during geomagnetically moderate and active times